Pengaruh Model Problem Based Leraning Pendekatan Metakognitif Terhadap Kemampuan Pemecahan Masalah Pada Materi Bangun Datar Segiempat di Kelas VII SMP Muhammadiyah Tilango - Kaune, Nurlaila; Majid; Yahya, Lailany (Program Studi Pendidikan Matematika, Universitas Islam Negeri Raden Fatah Palembang, 2023)
This research aims to determine the effect of the problem based learning (PBL) model with metacognitive approach to problem solving ability on quadrilateral at seventh grade of junior high school students. The research method used is quantitative method with an experimental design, namely a posttest control design only. This research consisted of an experimental class with treatment using PBL model with metacognitive approach and control class with treatment using PBL model without metacognitive approach. The instrument in this research uses a mathematical problem solving ability test in the form of a description test. The results of research and information processing show that learning using PBL model with metacognitive approach has an influence on students' mathematical problem solving abilities. From the results of the inferential analysis of hypothesis testing using the two-sample t test, it can be seen that Ho is rejected and H1 is accepted because it meets the test criteria for tcount > ttable, 1.882 > 1.68195. So, it can be concluded that the mathematical problem solving ability of students who are taught using PBL model with metacognitive approach are higher compared to classes without metacognitive approach.